2004
DOI: 10.1116/1.1819926
|View full text |Cite
|
Sign up to set email alerts
|

Strain and electrical characterization of metal-oxide-semiconductor field-effect transistor fabricated on mechanically and thermally transferred silicon on insulator films

Abstract: Articles you may be interested inCharacterization of current injection mechanism in Schottky-barrier metal-oxide-semiconductor field-effect transistors Appl. Phys. Lett. 95, 083502 (2009); Electrical effects of a single stacking fault on fully depleted thin-film silicon-on-insulator P-channel metal-oxide-semiconductor field-effect transistors Nitrided thermal SiO 2 for use as top and bottom gate insulators in self-aligned double gate silicon-on-insulator metal-oxide-semiconductor field effect transistor Unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that layer-transferred Si on an oxidized Si wafer exhibits an initial compressive stress that is subsequently released after a 1000 C anneal [10]. If similar stress relaxation occurred in SOQ at the annealing temperature, then a thermallyinduced residual tensile strain of 0.2% could be deduced using the respective CTEs of and for Si and quartz.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that layer-transferred Si on an oxidized Si wafer exhibits an initial compressive stress that is subsequently released after a 1000 C anneal [10]. If similar stress relaxation occurred in SOQ at the annealing temperature, then a thermallyinduced residual tensile strain of 0.2% could be deduced using the respective CTEs of and for Si and quartz.…”
Section: Resultsmentioning
confidence: 98%
“…After the exfoliation, 70-100 nm of the transferred Si was removed by chemical-mechanical polishing and 168 nm with an average surface roughness of 0.7 nm was retained. The SOQ was subsequently annealed at 600 C for 60 min and 1000 C for 60 min in nitrogen, to recover the original p-type conductivity [10] and to enhance the bonding strength.…”
Section: Mechanical Exfoliation and Fet Fabricationmentioning
confidence: 99%